Analysis of the most efficient horizontal drainage position in the large strain consolidation considering the self-weight effect. (February 2023) - Xu, Chun-Tai; Wang, Zhong-Jin; Xie, Xin-Yu; Zheng, Ling-Wei
Abstract: To study the large-deformation settlement of soft soil foundations, an analysis of the large-strain consolidation of soil in a Lagrangian coordinate system based on continuum mechanics is performed, and the control equations with the displacement gradient are obtained in this paper. Based on the nonlinear permeability and compressibility of soft soil foundations, the equation of large-strain nonlinear consolidation is established. Then, the finite difference method is used to solve the governing equations. Under the condition of two-sided drainage while considering the soil self-weight stress, it is found that the distribution of excess pore pressure is not symmetric along the depth of the foundation. The position of the maximum excess pore pressure appears below the midpoint of the soil foundation. The deviation degree increases with increasing foundation thickness and semilogarithmic compression index C c value, and it decreases with increasing semilogarithmic permeability index C k value. The calculations show that setting the drainage layer position close to the position of maximum excess pore pressure can effectively improve the drainage ability of the upper and bottom soil layers, which is beneficial to consolidation, and that the deviation distance is related to the C c and C k values.